Disposal of syringes, needles, and lancets used by diabetic patients in Pakistan - Osama Ishtiaq; Asif Mehmood Qadri; Saeed Mehar; Ghulam Murtaza Gondal; Tahir Iqbal; Sobia Ali; Mati-; Naveed Zafar Janjua (Elsevier, 2012)
Summary: Objective: To assess the use, handling and disposal of insulin injection equipment by diabetic patients in Pakistan. Methods: We conducted a cross-sectional study at diabetic clinics in five tertiary centers in Pakistan. All diabetic patients (type 1/type 2) who were on insulin for more than 1 month, were included. An Urdu (local language)-translated questionnaire was used to collect information on insulin administration equipment, the site and frequency of needle use, insulin syringe/pen/lancet disposal, sharing of needles and knowledge about diseases that are spread by sharing contaminated needles. Results: Of 375 patients, 58% were female. The mean (SD) duration of diabetes was 12.3 (7.3) years, and the duration of insulin use was 4.4 (4.3) years. The majority of the patients used syringes (88.3%) for insulin administration. Additionally, the majority of the patients disposed of used devices (syringes, 92%; pens, 75%; and lancets, 91%) in the household garbage collection bin. About half of the patients (n = 185) reported being educated by their physicians about the disposal of sharps. Those who were educated by a physician (adjusted odds ratio (adjOR): 0.36; 95%CI: 0.16-0.81) or could read/write English (adjOR: 0.32; 95%CI: 0.11-0.92) were less likely to dispose of syringes and needles in the household garbage. Conclusion: The common disposal of sharps in the household garbage has implications for disease transmission. Education on the safe disposal of sharps may improve the disposal practices. Keywords: Diabetes mellitus, Disposal practices, Insulin syringe, Lancets, Insulin pens